A Different Perspective for Management of Diabetes Mellitus: Controlling Viral Liver Diseases - Yingying Zhao; Huichun Xing (Journal of Diabetes Research)
Knowing how to prevent and treat diabetes mellitus (DM) earlier is essential to improving outcomes. Through participating in synthesis and catabolism of glycogen, the liver helps to regulate glucose homeostasis. Viral related liver diseases are associated with glycometabolism disorders, which means effective management of viral liver diseases may be a therapeutic strategy for DM. The present article reviews the correlation between DM and liver diseases to give an update of the management of DM rooted by viral liver diseases.